Social Media and Education 2019
DOI: 10.4324/9781315121697-6
|View full text |Cite
|
Sign up to set email alerts
|

Technology, time and transition in higher education – two different realities of everyday Facebook use in the first year of university in the UK

Abstract: http://shura.shu.ac.uk Technology, time and transition in higher educationtwo different realities of everyday Facebook use in the first year of university in the UKWithin the range of websites and apps that are part of first-year undergraduates' digital environments, the social network site Facebook is perhaps the most popular and prominent. As such, the ubiquitous nature of Facebook in the higher education landscape has drawn much attention from scholars. Drawing on data from a longitudinal connective ethnogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Many universities adopt or create digital social networks to support students during this transition period and help them make new friends [ 7 , 8 ]. Stirling [ 35 ] describes the use of social networks (SNs) by students as an organisational as well as communicative tool in their early university encounters. An absence of peer networks are associated with early drop-out or poor student performance [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many universities adopt or create digital social networks to support students during this transition period and help them make new friends [ 7 , 8 ]. Stirling [ 35 ] describes the use of social networks (SNs) by students as an organisational as well as communicative tool in their early university encounters. An absence of peer networks are associated with early drop-out or poor student performance [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study found that social media sites are students' 'daily bread' (from home to school), and that they are effective for learning because they improve interaction among peers and lecturers for content dissemination. The findings of these and other studies (Bradwell, 2009;Mpungose, 2020;Stirling, 2016) suggest that universities should gradually move from formal educational technologies (LMS) to informal ones like social media sites, VCTs and others as students enjoy informal spaces (Basitere and Mapatagane, 2018).…”
Section: Research Context Sample Design and Paradigmmentioning
confidence: 90%
“…The students positioned themselves as 'subordinates' and essentially silenced themselves in this sphere; this occurred despite the fact that it was in the context of an initiative designed to empower and give voice to the students. Social media in HE contexts comes with a complex bundle of expectations and associations, and can be seen by students as antiacademic (Stirling, 2016). Other researchers are careful to stress that the overarching learning design is more important than the devices that are involved in the learning experience (Laurillard, 2009;Pimmer et al, 2016;Lai et al, 2016).…”
Section: Social Media and Higher Education: Potentials And Pitfallsmentioning
confidence: 99%